2011
DOI: 10.1097/rct.0b013e31821e277b
|View full text |Cite
|
Sign up to set email alerts
|

Surfer's Myelopathy-Demonstrated by Diffusion-Weighted Magnetic Resonance Imaging

Abstract: The authors present a case of "surfer's myelopathy," a rarely described syndrome characterized by nontraumatic paraparesis/paraplegia in novice surfers and theorized to result from spinal cord ischemia secondary to surfing-related positional hyperextension. Imaging and clinical course of the youngest known affected individual are discussed, including evidence of acute spinal cord infarction on diffusion-weighted magnetic resonance imaging, a finding not previously described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…A few studies have demonstrated increased diffusion restriction on DWI correlating with decreased signal on ADC mapping in surfer’s myelopathy, supporting the hypothesis that the T2-signal abnormalities represent cytotoxic edema in the setting of an acute spinal cord infarction. 8,10 Conventional spinal angiograms were normal when performed in previously described cases. 1,5,10 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A few studies have demonstrated increased diffusion restriction on DWI correlating with decreased signal on ADC mapping in surfer’s myelopathy, supporting the hypothesis that the T2-signal abnormalities represent cytotoxic edema in the setting of an acute spinal cord infarction. 8,10 Conventional spinal angiograms were normal when performed in previously described cases. 1,5,10 …”
Section: Discussionmentioning
confidence: 88%
“…Five published papers detailed the time between symptom onset and imaging, and conventional spinal cord MR imaging was abnormal within 2–12 hours. 1,2,4,5,8 One case reported by Kelly and Wright 3 was initially normal but was subsequently abnormal on repeat imaging within 24 hours of the initial MR imaging. 3 DWI with ADC mapping has inconsistently demonstrated restricted diffusion in cases of surfer’s myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…MRI-DWI itself is highly sensitive to detecting acute cellular injury due to the changes in water diffusion present secondary to the ischaemia (11). In both studies in the inclusion of gadolinium contrast did not facilitate diagnosis, but was justified as a means of excluding differentials.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been 64 cases published since 2004, standardisation in the management algorithm of these patients is yet to be achieved (1,2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Several interventions have been proposed, including early steroid therapy and anticoagulation, though the rarity of cases has largely prevented quality research on the matter.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one cases of surfer's myelopathy have been described in the literature [3,[8][9][10][11][12][13][14][15][16]. These people develop progressive bilateral lower limb pain, paresthesia, and paraplegia during their first lesson.…”
Section: Surfer's Myelopathymentioning
confidence: 99%